Pemakaian Model Diterministik Untuk Transformasi Data Hujan Menjadi Data Debit Pada Das Lahor - Ernawan Setyono (Department of Civil Engineering, Faculty of Engineering, University of Muhammadiyah Malang, 2011)
Hydrologic analysis is an important stage in water resources development activities, therefore the output of the general hydrological analysis will determine the direction of water resources development strategy in a comprehensive and more narrow scale will determine the dimensions and characteristics of the necessary infrastructure. Determination of hydrological quantities are actually not too difficult when the data for analysis is available in sufficient quantity and quality. Classical problems in developing countries, including Indonesia, the availability of river flow data series is quite a separate issue, so the solution must be done by to specification climate variables into a variable flow. So far this has been developed conceptual model, of course, each has advantages and disadvantages because basically models were developed according to local hydrological conditions. All models are basically developed from the same basic concept, namely the hydrological cycle. Basic things that sets it apart is the way to interpret the process until the rain began to flow. This is what would need to be studied further in this study.This study is an attempt to determine the performance model determinstic of FJ Mock, NRECA, and Tank model and can explain the comparative level of performance of the deterministic model in Reservoir Lahor.Results of research on Lahor Reservoir indicated that the tank model is able to present the relationship of climate data and data streams very well. In this research obtained on the model RMSE value of model NRECA is 7.854 m3/sec, model FJ Mock for 18.696 m3/sec and Tank Model for 7.823 m3/sec.Keywords: discharge, NRECA model, fjmock model, model tank